THE CHANGES IN THE CONCENTRATION OF INTERLEUKIN-6 IN BLOOD AND BILE IN PATIENTS WITH OBSTRUCTIVE JAUNDICE AFTER BILE SORBTION - Aripova, N.U; Matmuratov, S.K.; Babadjanov, J.K (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: The study of the effect of the bile sorption on the change in the concentration of IL-6 in the blood and bile in patients with malignant mechanical jaundice. Material and methods: The 84 patients with malignant mechanical jaundice were studied. Patients are divided into two groups. The first group consisted of 41 patients. The second group consisted of 43 patients in whom, after the percutaneous transhepaticcholangiostomy, was performed bilesorption using the new domestic enterosorbentLignova. The level of IL-6 in serum and bile was determined by the ELISA method (set of production Vector-Best, Novosibirsk, Russia). Results:In the first group of patients, the concentration of IL-6 before the percutaneous transhepaticcholangiostomy in the serum was higher than normal, averaging 152.65 ± 16.3 pg/ml. Immediately after the percutaneous transhepaticcholangiostomy in bile, this indicator was on average 68.58 ± 7.24 pg/ml. At the end of the observation, the level of IL-6 a decreased in the blood compared to baseline -64.4%, and in bile 54.3% (P <0.001). In the second group of patients, after the percutaneous transhepaticcholangiostomy, the concentration of IL-6 in the serum averaged 151.52 ± 14.2 pg/ml, and in bile - 67.43 ± 9.14 pg/ml. Initially, a high concentration of IL-6 in blood and bile after perform of bile sorption decreased, respectively, by 75.7% (36.81 ± 4.4 pg / ml) and 73.9% (17.57 ± 2.2pg/ml) from the initial level. Inclusion in the medical complex of bile sorption significantly changed the concentration of IL-6 in the blood serum (P <0.01) and bile. Conclusion: The use of bile sorption contributes to a decrease of proinflammatory cytokine IL-6 in the blood and bile as an inducer of endogenous intoxication and a cascade of inflammatory processes in patients with biliopancreatoduodenal zone tumors complicated by mechanical jaundice.